2020
DOI: 10.1038/s41467-019-14261-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutational signatures in tumours induced by high and low energy radiation in Trp53 deficient mice

Abstract: Ionising radiation (IR) is a recognised carcinogen responsible for cancer development in patients previously treated using radiotherapy, and in individuals exposed as a result of accidents at nuclear energy plants. However, the mutational signatures induced by distinct types and doses of radiation are unknown. Here, we analyse the genetic architecture of mammary tumours, lymphomas and sarcomas induced by high ( 56 Fe-ions) or low (gamma) energy radiation in mice carrying Trp53 loss of function alleles. In mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Many chemicals induce DNA damage, thereby increasing the rate of potentially oncogenic DNA replication errors ( 2 ). The same is true for many forms of radiation ( 3 ). Nonmutagenic and nongenotoxic carcinogens act through a variety of secondary mechanisms such as inhibition of the immune system, cell-cycle overdrive to bypass normal DNA replication checkpoints, and induction of inflammation which may lead to both increased cellular proliferation and DNA damage, among others ( 4 ).…”
mentioning
confidence: 75%
“…Many chemicals induce DNA damage, thereby increasing the rate of potentially oncogenic DNA replication errors ( 2 ). The same is true for many forms of radiation ( 3 ). Nonmutagenic and nongenotoxic carcinogens act through a variety of secondary mechanisms such as inhibition of the immune system, cell-cycle overdrive to bypass normal DNA replication checkpoints, and induction of inflammation which may lead to both increased cellular proliferation and DNA damage, among others ( 4 ).…”
mentioning
confidence: 75%
“…However, this is often the case in any study and we included the clinical information on why subsequent malignancies were more consistent with recurrent disease rather than RT‐induced, which is often not described in the literature. In future work, the use of DNA sequencing and mutational signatures may be employed to reliably distinguish recurrent disease from radiation‐induced cancers 26‐28 . Another potential limitation is the limited follow‐up time.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these genomic studies provide compelling evidence to support a model in humans and mice without germline mutations where the formation of hematologic malignancies following exposure to ionizing radiation occurs through a non-cell-autonomous mechanism 8,46,47 . However, for individuals harboring germline mutations in DNA damage response genes, such as p53 and Mlh1 , ionizing radiation may cause blood cancers through a more direct cell-autonomous effect by increasing genomic instability in tumor-initiating cells 13,14,45 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, using a mouse model of B-cell lymphoma, Patel et al found that gamma-rays and heavy ion ( 56 Fe) radiation markedly increased the number of insertions and deletions (indels) per tumor only in mice lacking one allele of the mismatch repair gene Mlh1 (Mlh1 +/- ) 13 . Also, using mice carrying different loss of function alleles of the tumor suppressor p53, Li et al observed that the genomic landscape of radiation-induced cancers is influenced by radiation quality, germline p53 deficiency and tissue/cell of origin 14 . Collectively, findings from these genomic studies advance our understanding of mutational processes that underlie the development of radiation-induced cancers.…”
Section: Introductionmentioning
confidence: 99%